2022
DOI: 10.1101/2022.10.03.22280227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of anti-polyethylene glycol (PEG) antibodies in the allergic reactions and immunogenicity of PEG-containing Covid-19 vaccines

Abstract: The polyethylene-glycol (PEG)-containing Covid-19 vaccines can cause hypersensitivity reactions (HSRs), or rarely, life-threatening anaphylaxis. A causal role of anti-PEG antibodies (Abs) has been proposed, but not yet proven in humans. The 191 blood donors in this study included 10 women and 5 men who displayed HSRs to Comirnaty or Spikevax Covid-19 vaccines with 3 anaphylaxis. 118 donors had pre-vaccination anti-PEG IgG/IgM values as measured by ELISA, of which >98% were over background regardless of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
(154 reference statements)
0
7
0
Order By: Relevance
“…Regarding the prevalence of anaphylaxis, which entails death or disability in 1.7%, 40 the ~1.8 billion mRNA-LNP injections given worldwide in 3 years places even the lowest estimate of the sheer number of anaphylaxis cases in the multiple thousand range. Calculating with the median of estimated anaphylaxis rate (123 cases/million), 32 yields 223,200 anaphylaxis with ~3,800 death or disability worldwide, placing vaccine-induced anaphylaxis as the first pandemic of an iatrogenic rare (orphan) disease. To prevent its occurrence in the future, when new infection diseases and vaccines arise, the phenomenon needs to be understood.…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the prevalence of anaphylaxis, which entails death or disability in 1.7%, 40 the ~1.8 billion mRNA-LNP injections given worldwide in 3 years places even the lowest estimate of the sheer number of anaphylaxis cases in the multiple thousand range. Calculating with the median of estimated anaphylaxis rate (123 cases/million), 32 yields 223,200 anaphylaxis with ~3,800 death or disability worldwide, placing vaccine-induced anaphylaxis as the first pandemic of an iatrogenic rare (orphan) disease. To prevent its occurrence in the future, when new infection diseases and vaccines arise, the phenomenon needs to be understood.…”
Section: Clinical Relevancementioning
confidence: 99%
“…28 Regardless of C activation, the likely causal role of anti-PEG Abs in mRNA-LNP vaccineinduced HSRs/anaphylaxis was raised by many groups, 1,8,15,16,18,31 and we found significant correlation between the blood levels of anti-PEG Abs and rise of HSR/anaphylaxis in recipients of Comirnaty and Spikevax. 32 Nevertheless, all above facts provide only indirect proofs of a causal role of anti-PEG Abs in Comirnaty-induced HSRs; conclusive experimental or clinical evidence is still lacking. Accordingly, the goal of the present study was to obtain such evidence using the anti-PEG hyperimmune pig model, 33 which showed the acceleration of HSR to anaphylaxis to PEGylated liposomal doxorubicin (Doxil) if the blood level of anti-PEG IgM had been increased by prior vaccination with drug-free Doxil (Doxebo).…”
Section: Introductionmentioning
confidence: 99%
“…Generation of anti-PEG antibodies following vaccination with Spikevax (the mRNA vaccine manufactured by Moderna) and Comirnaty has been studied in four other recent studies, employing ELISA to detect the presence of the antibodies. While all of these studies (as well as a MedRxiv pre-print) found an increase in anti-PEG antibodies following vaccinations with Spikevax, , only two of the peer-reviewed studies reported an increase in anti-PEG antibodies following vaccination with Comirnaty, , and this increase was more modest compared to what was observed for the Moderna vaccine. We here expand on that knowledge, carried out in Southern European, Australian, North American, and Middle-Eastern populations, with a study performed in a Scandinavian population using a methodology looking at antibodies against the actual LNP as a whole entity and not against the individual lipid components alone.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the anti-PEG IgM measurements in our patient was done as part of a different project aimed to establish the risk of allergic people to develop anaphylactic reaction to Comirnaty, which contains PEG. 15 , 16 High blood levels of such antibodies have been implicated in the anaphylactic reactions to numerous PEGylated drugs, 17–19 , 33 , 34 Furthermore there is a suspicion that the increased occurrence of such reactions after mRNA vaccines 35–40 may be due, at least in part, to the presence of high levels of anti-PEG antibodies. 15 , 16 , 41 In fact, a recent study on 55 people receiving Comirnaty showed the common presence of anti-PEG IgG and IgM, which were boosted by vaccination by a mean of 2–3-fold, up to 13–17-fold in some individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-PEG IgM titers in blood were determined using a sandwich ELISA, as described previously. 17 …”
Section: Methodsmentioning
confidence: 99%